Hubungan Riwayat BBLR Dan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita 24-59 Bulan Di Puskesmas Kutawis - Anggi Nurin Kamarina; Prasanti Adriani; Arlyana Hikmanti (Universitas Harapan Bangsa Purwokerto, 2023)
Stunting is the impaired growth experienced by children under five due to chronic malnutrition and repeated infections in the first 1,000 days of life. Children under five with a height of < -2 SD are considered stunting. This study aims to identify the relationship between Low Birth Weight (LBW) and exclusive breastfeeding with the stunting incidences in children aged 24-59 months in Puskesmas Kutawis. This quantitative study used case-control and retrospective designs involving 76 samples divided into two, case and control groups with 38 children of each using purposive sampling techniques. Data were analyzed using the chi-square test and showed that children with LBW history were 20 (52.6%) in the case group and 5 (13.2%) in the control group. Children under five with exclusive breastfeeding were 13 (34.2%) in the case group and 31 (81.6%) in the control group. The results of the Chi-square test found that children under five with a history of LBW obtained p-values of 0.001 (OR = 7.333; 95% CI: 2.355-22.835) and the history of exclusive breastfeeding obtained p-values of 0.000 (OR = 8.516; 95% CI: 2.953-24.561). It can be concluded that there is a significant relationship between LBW and exclusive breastfeeding with stunting incidences in Puskesmas Kutawis where children with a history of LBW have risks of 7,333 times and those without exclusive breastfeeding have risks of 8,516 times.